Accelerating the 5G transition in Europe How to boost investments in transformative 5G solutions - Gilles, François (European Investment Bank, 2021)
This study discusses why the "fifth generation" of telecommunication systems, or 5G, is integral to digitalisation efforts, and how its roll-out will be one of the most critical building blocks of the European digital economy and society in the next decade. We examine the transformative properties of this technology and explore how we can ensure that Europe remains a relevant, competitive and strategically autonomous player on the global scene.